Non-invasive wearable devices in paediatric cancer care: Advancing personalized medicine, addressing challenges and shaping the future - Christa Koenig; Roland A. Ammann; Eva Brack (EJC Paediatric Oncology)
Wearable devices (WDs) are capable of collecting large volumes of objective and clinically relevant patient data that is not yet routinely captured. This ability to collect continuous, real-time data offers a unique opportunity to gather health information in new and insightful ways. In paediatric oncology, advancement in treatment have led to significant improvements in survival rates. However, aggressive therapies often result in a range of distressing side effects, which can severely impact quality of life, and even can become life-threatening themselves. Supportive care plays a crucial role in mitigating these symptoms, aiming to prevent and manage side effects. Patient-reported outcomes should be used to guide initiation and choice of supportive care treatment whenever possible. In this context, continuous monitoring of vital signs, physical activity and other health parameters using WDs could add individual, patient specific information regarding a patient’s current condition. In this article we discuss the requirements of non-invasive WDs for their use in paediatric oncology, give an overview on possible areas of application in children with cancer and discusses challenges that must be addressed. Also we identify key research gaps and speculate on future perspectives.